Achilles Tendinopathy and Associated Factors among Recreational Ballet Dancers: A Cross Sectional Study - Suvinlal Stalin Russel1, Tan Xin Yi2, Rahul Krishnan Kutty1, Syed Abudaheer Kajamohideen1, Arunkumar (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Achilles tendinopathy (AT) describes an overuse condition which common experienced bydancers. The reason is because dance is a physical activity involving short explosive runs, turns, jumps,leaps and weight bear on metatarsal heads which forcefully contract the calf muscles and this causes morepressure on Achilles tendon. However, lack of studies on AT in dancers has been reported.Objectives: To find out the prevalence and risk factors of Achilles tendinopathy among recreational balletdancers.Method: Quantitative approach, non- experimental and descriptive research design was conduct on a sampleof 53 female and male recreational ballet dancers. Ages varied from 15- 30 and at least with 2 years ofballet dancing experiences were selected by purposive sampling from the ballet dance company or studios.Screening tools and prevalence sheet priority given to the subjects to fill in to select appropriate populationwho passed the study’s inclusion and exclusion criteria. Then researcher required to palpate the Achillestendon area to confirm the problem before distribute the questionnaire form to ballet dancers. All the datawere using percentage and mode to analyze. Results: Our findings show 28.3% of the recreational balletdancers had AT and footwear is the highest average risk factors among training duration, limited warm upand cool down, and muscle strength. Besides that, our findings also show BMI, unfamiliar choreography,training surface, medication, flexibility and lower limb abnormalities are not the risk factors that cause themto have AT.Conclusion: AT is common among recreational ballet dancers and footwear is the highest average of riskfactors among the four risk factors. These findings provide clearlyInformation for dancers, teachers, sport therapists, health professionals and parents to prevent or treat theinjuries more effectively and help to develop strategies aimed at reducing the prevalence of ballet injuries.